2018
DOI: 10.1021/acs.jnatprod.7b00698
|View full text |Cite
|
Sign up to set email alerts
|

Nitrobenzoyl Sesquiterpenoids with Cytotoxic Activities from a Marine-Derived Aspergillus ochraceus Fungus

Abstract: Nitrobenzoyl sesquiterpenoids are rare from natural sources. Two new nitrobenzoyl sesquiterpenoids, insulicolide B (1) and insulicolide C (3), and the new natural product 14-O-acetylinsulicolide A (2) were isolated from culture extracts of the marine-derived fungus Aspergillus ochraceus Jcma1F17, together with three known nitrobenzoyl sesquiterpenoids (4-6) and a derivative sesquiterpenoid (7). The structures of the new compounds, including their absolute configurations, were determined by NMR and MS spectrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 12 publications
1
67
0
Order By: Relevance
“…The extraction process and structures of nitrobenzoyl sesquiterpenoids were described in our previous study (Tan et al, 2018).…”
Section: Reagents and Antibodiesmentioning
confidence: 99%
“…The extraction process and structures of nitrobenzoyl sesquiterpenoids were described in our previous study (Tan et al, 2018).…”
Section: Reagents and Antibodiesmentioning
confidence: 99%
“…Compounds 14-O-acetylinsulicolide A (31), 6β,9α-dihydroxy-14-p-nitrobenzoylcinnamolide (29) and insulicolide A (30) (Figure 1) displayed activities with IC 50 values of 0.89 to 8.20 µM. Further studies indicated that compound 31 arrested the cell cycle at the G0/G1 phase at a concentration of 1 µM and induced late apoptosis at a concentration of 2.00 µM after a 72-h treatment of 786-O cells [41]. Therefore, the nitrobenzoyl sesquiterpenoids have attracted attention of researchers, because of their good antitumor potential.…”
Section: Terpenoidsmentioning
confidence: 99%
“…Compounds 29 and 30 displayed significant cytotoxicity against 10 human cancer cell lines, with IC 50 values of 1.95 to 6.35 µM [40]. There are few nitrobenzoyl sesquiterpenoids reported in the literature, most of them being obtained from fungi of the genus Aspergillus of marine origin that were isolated from sediment [73], and from marine organisms such as seaweed [40,41,72] and sponges [73].…”
Section: Terpenoidsmentioning
confidence: 99%
“…Marine-derived fungi are reported as a prodigious source of development for new antivirals against different important viruses (Moghadamtousi et al, 2015 ). In our continuing endeavor to discover biologically active compounds from marine microbes, a series of structurally interesting and biologically active natural products have been described (Luo et al, 2017 ; Tan et al, 2018 ). Recently, six new cytotoxic chloroazaphilone derivatives, isochromophilones A–F, have been isolated from the fungus Diaporthe sp.…”
Section: Introductionmentioning
confidence: 99%